The messy lives of book people - Patrick, Phaedra (Park Row Books, 2022)
"Mother of two Liv Green barely scrapes by as a maid to make ends meet, often finding escape in a good book while daydreaming of becoming a writer herself. So she can't believe her luck when she lands a job housekeeping for her personal hero, megabestselling author Essie Starling, a mysterious and intimidating recluse. The last thing Liv expected was to be the only person Essie talks to, which leads to a tenuous friendship. But when Essie dies suddenly, a devastated Liv is astonished to learn of her last wish: for Liv to complete Essie's final novel. But to do so Liv will have to step into Essie's shoes, and as Liv begins to write, she uncovers secrets from the past that reveal a surprising connection between the two women--one that will change Liv's own story forever..." -- Back cover.